2018
DOI: 10.1680/jmapl.17.00052
|View full text |Cite
|
Sign up to set email alerts
|

An ontology-based data integration framework for construction information management

Abstract: Information management during the construction phase of a built asset involves multiple stakeholders using multiple software applications to generate and store data. This is problematic as data come in different forms and are labour intensive to piece together. Existing solutions to this problem are predominantly in proprietary applications, which are sometimes cost prohibitive for small engineering firms, or conceptual studies with use cases that cannot be easily adapted. In view of these limitations, this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Also, it can reduce the time and cost spent in visiting multiple authorities (Meacham et al 2019). Besides, (Akinyemi et al 2018) revealed in their study that leveraging information integration technologies in construction sector can be beneficial as reveals that by adopting online web technologies can make substantial savings in time when compared to traditional information management approach. The process time using electronic permitting system for construction projects can be slashed up to 25 days (Shahi 2018).…”
Section: Literatures Reviewmentioning
confidence: 99%
“…Also, it can reduce the time and cost spent in visiting multiple authorities (Meacham et al 2019). Besides, (Akinyemi et al 2018) revealed in their study that leveraging information integration technologies in construction sector can be beneficial as reveals that by adopting online web technologies can make substantial savings in time when compared to traditional information management approach. The process time using electronic permitting system for construction projects can be slashed up to 25 days (Shahi 2018).…”
Section: Literatures Reviewmentioning
confidence: 99%
“…Conceptual [27], [28], [29], [30], [31], [32] [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45] 70% Empirical [46], [47], [48], [49], [50], [51] [52], [53] 30% Share 56% 44%…”
Section: Has Methods Chapter No Methods Chapter Sharementioning
confidence: 99%
“…Besides providing formal domain knowledge representation, another use of ontologies in the construction domain is to address the problem of data integration [42][43][44]. Information heterogeneity remains a common domain issue [45] and has huge effects on establishing the digital twin construction (DTC).…”
Section: Ontology and Digital Twin Constructionmentioning
confidence: 99%